Machining performance of ceramic tool inserts during dry turning of hardened steel - K. I. Vishnu Vandana; P. Siva Nagasree (Universitas Mercu Buana, 2024)
For effective dry turning of hardened steels, ceramic tool materials have long been utilized as an alternative to conventional tool materials. Therefore, the purpose of the current work is to investigate whether ceramic materials like alumina (Al2O3) are suitable for use as tool materials during the dry (without coolant) turning of hardened steels. In addition, while cutting EN 24 hardened steels, the performance of an alumina ceramic tool insert was compared to a commercial tool insert in the current work. On EN 24 steel samples, turning operations were performed utilizing both alumina ceramic tool inserts and commercial carbide tool inserts at different machining parameters such as speed, feed, and depth of cut. The turning performance of both alumina and commercial tool inserts was evaluated at various machining conditions based on abrasive wear (weight loss) of the tool inserts and the surface roughness of EN 24 machined samples. At all machining parameters, it was found that the abrasive wear of ceramic tool inserts was lower than the abrasive wear of commercial tool inserts. It is observed that, the surface roughness of EN 24 machined samples when machined with ceramic tool inserts was a little higher when compared with the surface roughness values of EN 24 machined samples which are machined with the commercial tool insert. The results of the experiment showed that ceramic cutting tools had comparable cutting performance to commercial cutting tools.